Second Primary Pancreatic Adenocarcinoma Three Years After Successfully Treated Index Esophageal Cancer - Nandy, Nina; Dasanu, Constantin A (JOP. Journal of the Pancreas, 2014)
Context Development of a second primary malignancy after an index esophageal cancer is a rare event, primarily due to short survival of patients with esophageal cancer. However, the number of long-term esophageal cancer survivors has been increasing due to advances in early detection and therapy. Case report We report herein a case of pancreatic adenocarcinoma that developed three years after a successfully treated early-stage adenocarcinoma of the esophagus. A 70-year-old Caucasian male presented with vague complaints of nausea, vomiting and abdominal distention, with subsequent development of jaundice. A computed tomography scan of abdomen revealed a 2.9 cm soft tissue mass in the head of the pancreas and the patient underwent a Whipple’s procedure, with pathology confirming the diagnosis of pancreatic adenocarcinoma. Three years previously, the patient was successfully treated for adenocarcinoma of the esophagus via minimally invasive esophagogastrectomy. Despite chemoradiotherapy for localized disease and subsequent systemic chemotherapy for metastatic pancreatic cancer, the patient eventually succumbed to his illness. Conclusion We discuss the association between esophageal cancer and subsequent second malignancies, along with implications for surveillance and therapy. Image: A low-attenuation mass in the head of the pancreas and uncinate process.